2008
DOI: 10.1124/dmd.107.019513
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Terpenoids on Multidrug Resistance-Associated Protein 2- and Breast Cancer Resistance Protein-Mediated Transport

Abstract: ABSTRACT:The possibility of interactions between natural products/supplements and conventional prescription medicines is one of the most important issues in pharmacotherapeutic safety. Recently, we reported that some terpenoids such as (R)-(؉)-citronellal and glycyrrhetic acid, which are present in herbal medicines, can act as inhibitors of P-glycoprotein (MDR1/ABCB1). In the present study, the effects of seven terpenoids on multidrug resistance-associated protein 2 (MRP2/ABCC2) and breast cancer resistance pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…E 2 17βG is a well known substrate for the study of MRPs (such as MRP1, MRP2, MRP3, MRP4 and MRP7); in recent years, studies had shown that it could be transported by Pgp, BCRP and OATP as well. Regardless, E 2 17βG has a significantly higher affinity toward MRP1 and MRP2 compared to other transporters (38)(39)(40)(41). Despite the high affinity of E 2 17βG with MRP1, there is a considerably lower expression level of MRP1 compared to MRP2 in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 77%
“…E 2 17βG is a well known substrate for the study of MRPs (such as MRP1, MRP2, MRP3, MRP4 and MRP7); in recent years, studies had shown that it could be transported by Pgp, BCRP and OATP as well. Regardless, E 2 17βG has a significantly higher affinity toward MRP1 and MRP2 compared to other transporters (38)(39)(40)(41). Despite the high affinity of E 2 17βG with MRP1, there is a considerably lower expression level of MRP1 compared to MRP2 in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 77%
“…The transporter spectrum of some saponins may overlap with those of statins. For example, ginsenoside Rh 2 isolated from ginsenoside is a substrate of BCRP (Jin et al, 2006), and glycyrrhetic acid derived from licorice is a moderate inhibitor of MRP2 and BCRP (Yoshida et al, 2008). Although this overlap may lead to potential DDI issues, no studies or clinical reports examining these issues have been published.…”
Section: Discussionmentioning
confidence: 94%
“…Natural Products. Several diet-derived/natural product constituents, such as curcumin, daidzein, genistein, chrysin, 7,8-benzoflavone, and glycyrrhetic acid, have been shown to inhibit human BCRP in vitro (Zhang et al, 2005a;Yoshida et al, 2008;Merino et al, 2010;Tamaki et al, 2010). In addition, a mixture of the soy isoflavones genistein and daidzein was shown to inhibit Bcrp in wild-type but not Bcrp-knockout mice, supporting specificity for Bcrp inhibition (Merino et al, 2010).…”
Section: Orgmentioning
confidence: 99%